Green Synthesis of Silver Nanoparticles Using Catharanthus roseus Flower Extracts and the Determination of Their Antioxidant, Antimicrobial, and Photocatalytic Activity - Mathivathani Kandiah; Kavishadhi N. Chandrasekaran (Journal of Nanotechnology)
The present study describes the antioxidant, antimicrobial, and photocatalytic activity of silver nanoparticles (AGNPs) synthesized using six varieties of Catharanthus roseus flower extracts for the first time. Initially, the synthesized AgNPs were visually confirmed by color change. Further, the formation, size, and shape of the synthesized AgNPs were characterized by UV-Vis spectroscopy and scanning electron microscopy (SEM). The SEM image of purple flower AgNPs and the calculated bandgap energies of the synthesized AgNPs showed that the synthesized AgNPs were in the range of 0–30 nm. Qualitative phytochemical analysis revealed the presence of the phytocompounds that were responsible for the capping, formation, bioreduction, and stabilization of AgNPs. The antioxidant ability of the AgNPs and their respective flower extracts were analyzed using TFC, TPC, TAC, DPPH, FRAP, and IC50 assays. The results of the antioxidant assays indicated that the AgNPs showed higher antioxidant activity compared to their respective flower extracts. The synthesized AgNPs showed significant antimicrobial activity against Gram-negative Escherichia coli compared to Gram-positive Staphylococcus aureus assayed using the agar well diffusion method. Furthermore, the photocatalytic activity of the synthesized purple flower AgNPs at two different concentrations 5000 ppm and 333 ppm was analyzed by the removal of methyl orange dye from an aqueous solution under sunlight irradiation in the presence of NaBH4 catalyst. Results indicated that 333 ppm purple flower AgNPs exhibited an efficient photocatalytic activity in the degradation of methyl orange compared to 5000 ppm purple flower AgNPs in 20 minutes. Thus, the results obtained indicated that Catharanthus roseus is an ecofriendly source for the green synthesis of AgNPs which can be used as a novel antioxidant, antimicrobial, and photocatalytic agent; thereby, it can be used in a variety of applications to improve the quality of human life.